Performance Evaluation of Analytic Hierarchy Process Method in the Optimization of Welding Parameters - U. E. Affe; J. Ejonobo (Journal of Applied Sciences and Environmental Management, 2025)
Obtaining an optimal weld with the required properties is important, as it impacts directly on the durability and lifespan of the product which are factors considered in accessing its quality. This study focuses on the evaluation of the performance of Analytic Hierarchy Process (AHP) method in the optimization of welding parameters. Three input parameters; weld current, arc voltage, and gas flow rate were selected for this study, together with the following responses; tensile strength, hardness, and yield strength. From the results of the analysis using AHP, the following were obtained; arc voltage 25volts, weld current 190 amp, and gas flow rate of 15lt/min, has the highest weight of 0.463 equivalent to 43%.